Görsel medya bağlamında 32. Gün haber programında Ağca Dosyası örneği - Köken, Necdet (My University, 2007)
GÖRSEL MEDYA BAĞLAMINDA 32.GÜN HABER PROGRAMINDA AĞCA DOSYASI ÖRNEĞİ Televizyonun haber sunumu haberde görüntünün önem kazanmasını sağladı. Görüntünün ve sesin bir arada verilmesi olanağı görsel medyadaki haberin değerini arttırdı. Bu değerin artmasında bir diğer etken de haberin hızlı sunulabilmesidir. Televizyonun herkese hitap edebilmesi ve haberi almak için sadece izlemenin yeterli olması, haber ediminde hem kolaylığı hem de eşitliği sağladı.Televizyon haberciliğinde görüntünün önem kazanması ayrıca haberleri birer kurgu ve görsel şova dönüştürmeye başladı. Televizyonun zamansal sınırlılığı haberi belli süreye ayarlı ürüne dönüştürür. Haberde metinsel yazın ile görüntü süresinin birbirine uyumu sağlanarak yapılsa da daha çok anlatım görüntüye uydurulur. Çünkü önemli olan görüntüdür. Görsel medyada haberin ilgi görmesi televizyonda daha çok haber verilmesini sağladı. Haberde çeşitlilik arttı. Kuşak haberler, haber programları ve reality show’lar türü haber programları ortaya çıktı. Kuşak haberler belli saatlerde günün gelişen olaylarını aktarırlar. Reality Show’lar daha çok kurgulanmış ve ilgi çekmesi için şiddet içerikli haberin sıkça işlendiği progamlardır. Haber programları ise belli bir konuyu hikayeleme şeklinde yada detaylandırarak sunan programlardır. Ülkemizde de haber programları denince ilk akla gelen 32.Gün haber programıdır. 32.Gün’de yayınlanan M.Ali Ağca dosyası haber programlarının nasıl yapıldığı üzerine bir örnektir. Bu dosyada M.Ali Ağca’nın hayat hikâyesi ve karıştığı eylemler görsel medya bağlamında işlenmiştir.Bu tez çalışmasında M.Ali Ağca dosyasının nasıl işlendiği üzerine bir inceleme yapıldı. İnceleme yapılırken de televizyonun ve haber programlarının mantığı göz önüne alındı.

THE EXAMPLE OF AĞCA FILE IN THE “32. GÜN” NEWS PROGRAMME IN RELATION TO VISUAL MEDIA The news broadcasting on the televison has made the visual aspects in a piece of news important. The opportunity of having image and sound together increased the value of news in the visual media. Another impact which increased the value was the accelerated presentation of the news. The fact that the television addresses everyone and that it is enough to simply watch to receive the news have facilitated the news provision, as wlel as making it more egalitarian. The importance shift in the tv correspondence towards images has also made the news an editting and visual show of some kind. The limited time scope of the tv transforms the news into a product of a certain time period. Even if the text and image duration are one to one matched in a piece of news, still, most often it is the narrative being changed in order to fit the images, because it is the image that is of utmost importance. The shifting attention to the news in the visual media enabled an increase in the amount of news being broadcast on tv. The news diversified. Breaking news, news news programmes and reality shows were among the new types of news programmes. The breaking news inform about the spot events of a certain period of time. Reality shows are more fictitious and contain elements of violence in order to attract attention. News programmes on the other hand, narrate a certain subject matter or they provide further details about a theme. In Turkey, “32. Gün” (The 32nd Day) is the news programme that comes to mind first when it comes to news programmes. The M. Ali Ağca file presented on “32. Gün” is an example, demonstrating how the news programmes are made. In the file, the life story of M. Ali Ağca and the acts he was charged with are being handled within the context of visual media. In my graduate thesis study, the way how M. Ali Ağca file was presented has been examined. During the examination, the mentality of the television and news programmes was taken into account.
Keywords: 32. Gün Haber Programı; Ağca, Mehmet Ali; Haber Programları; Televizyon Programları